Rebranding Cesky Cookies Sebagai Inovasi UMKM Berkelanjutan Di Kelurahan Gunung Anyar Tambak - Alief Abdullah Faqih; Sugito Sugito (Jurnal Nusantara Berbakti, 2023)
Rebranding is a strategic process to change the image, identity, and position of a brand or company with the aim of achieving better business goals. Then the KKN activity aims to rebrand Cesky Cookies MSMEs in Gunung Anyar Tamba Village due to a response to increased customer interest in innovation product Activity methods used include observation, interviews, data analysis, and product rebranding. And the results of this PKM are changes to the logo, re-photos of products, and making branding banners. It is hoped that this activity can increase product attractiveness and have a positive impact on brand image and awareness among customers